Transcriptomic responses of mixed cultures of ascomycete fungi to lignocellulose using dual RNA-seq reveal inter-species antagonism and limited beneficial effects on CAZyme expression - Daly, Paul; van Munster, Jolanda M.; Kokolski, Matthew; Sang, Fei; Blythe, Martin J.; Malla, Sunir; Velasco de Castro Oliveira, Juliana; Goldman, Gustavo H.; Archer, David B. (Elsevier, 2017)
Gaining new knowledge through fungal monoculture responses to lignocellulose is a widely used approach that can lead to better cocktails for lignocellulose saccharification (the enzymatic release of sugars which are subsequently used to make biofuels). However, responses in lignocellulose mixed cultures are rarely studied in the same detail even though in nature fungi often degrade lignocellulose as mixed communities.